Transformasi Konsep Mahar dalam Kifayatul Akhyar Studi Komparatif Fiqh Islam dan Hukum Keluarga Indonesia - A Ansari (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This research is motivated by the change in the meaning and practice of dowry in Indonesian Muslim society, which shows a shift from classical understanding as enshrined in Kifayatul Akhyar to modern concepts in national family law. In Islamic fiqh, dowry is seen as a husband's moral and financial obligation to his wife as a form of responsibility and respect. However, in the contemporary socio-legal context of Indonesia, dowry has undergone a transformation into a symbol of equality, love, and sincerity between the two parties. The purpose of this study is to examine the conceptual comparison between Islamic fiqh views and the Indonesian family law arrangement regarding dowry, as well as to explore the factors driving this transformation. This study uses a qualitative type of research with a comparative-normative approach. Meanwhile, data collection is carried out through library research sourced from classical fiqh literature, laws and regulations, and modern academic studies. The results of the study show that the transformation of the concept of dowry is a consequence of the interaction between Islamic values, social dynamics, and the principle of gender justice in national law. Thus, the concept of dowry in Indonesian family law is not only rooted in classical fiqh, but also adapts to the spirit of maqāṣid al-syarī'ah to realize justice, equality, and benefits in the relationship between husband and wife.